2001
DOI: 10.1111/j.1572-0241.2001.03474.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of folate supplementation on two provisional molecular markers of colon cancer: a prospective, randomized trial

Abstract: Both of these provisional biomarkers of colon cancer underwent accelerated improvement at 6 months with folate supplementation. However, these markers also improved with placebo at 1 yr. Therefore, potential confounding factors that seem to modulate these biomarkers need to be identified and corrected in order for these markers to serve as suitable surrogate endpoints in folate chemoprevention trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
2
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(54 citation statements)
references
References 56 publications
2
48
2
2
Order By: Relevance
“…This is in contrast with an earlier study that observed a decrease of 35% with a 5 mg day À1 folic acid supplementation (Kim et al, 2001). Our participants, at baseline however, had no evidence of folate deficiency and, in fact, had generally higher concentrations of folate compared to earlier studies (Selhub et al, 1993(Selhub et al, , 1999.…”
Section: B-vitamin Deficiencycontrasting
confidence: 99%
See 2 more Smart Citations
“…This is in contrast with an earlier study that observed a decrease of 35% with a 5 mg day À1 folic acid supplementation (Kim et al, 2001). Our participants, at baseline however, had no evidence of folate deficiency and, in fact, had generally higher concentrations of folate compared to earlier studies (Selhub et al, 1993(Selhub et al, , 1999.…”
Section: B-vitamin Deficiencycontrasting
confidence: 99%
“…Five of the participants, all in the treatment group, reported increased constipation (P ¼ 0.056). (Kim et al, 2001). Thiamin was assessed at the time of entry to the study by the Reference Laboratory, St Joseph's Hospital, London, Ontario, Canada.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Cravo et al 53,54 observed that folate supplementation significantly reversed genomic DNA hypomethylation of the colonic mucosa. Kim et al 55 reported that DNA methylation underwent improvement with folate supplementation. However, methylation also improved with a placebo, which might have been caused by participants who were informed about the possible cancer-protective effects of folate.…”
Section: Discussionmentioning
confidence: 99%
“…Low dietary FA intake also results in an interruption of the DNA repair capability (Wei et al, 2003). The majority of prospective and case-controlled studies showed that low levels of serum FA, red cell FA concentration and low dietary FA intake are inversely correlated with colon cancer, breast cancer, adenoma and other cancers at several sites (Kim et al, 2001;Wang et al, 2006;Lin et al, 2010;Johnson et al, 2011).…”
Section: Interactions Between Mthfr C677t -A1298c Variants and Folic mentioning
confidence: 99%